“A Disturbing Lack of Musical and Stylistic Continuity”? Elliott Carter, Charles Ives, and Musical Borrowing - Thurmaier, David (Current Musicology, 2013)
Elliott Carter and Charles Ives shared a complex personal and professional relationship. Ives supported Carter’s musical pursuits as a young man and remained a guiding influence throughout his career. As Jan Swafford writes, however, “Carter, whose mature music would owe a great deal to Ives . . . would pay back his mentor with a baffling mixture of admiration, advocacy, and cold repudiation” (Swafford 1998: 334). Although he eventually softened his early criticism of Ives and acknowledged his musical debts, Carter was consistently puzzled by the stress in Ives’s music on musical borrowing—i.e., the procedures by which a composer includes material from or refers to pre–existing musical pieces in the context of an original work. As Carter put it, Ives’s reliance on quotations accounted for “a disturbing lack of musical and stylistic continuity” (Perlis 1974: 145). On another occasion, Carter described Ives’s inclusion of popular songs and hymns as “constantly perplexing” (Edwards 1971: 63). In view of these and numerous other statements, it is equally perplexing that Carter borrows from Ives’s music on several occasions, most overtly in his 2001 Figment No. 2 (Remembering Mr. Ives) for solo cello. This composition contains literal snippets and gestures from, as well as stylistic allusions to, two Ives pieces: the Concord Sonata and Hallowe’en. In what follows, I explore the ways in which Carter borrows from Ives both literally and figuratively; how he incorporates those quotations into his music; and how he evokes Ives’s memory and musical style in several works.